Pengembangan Lembar Kerja Peserta Didik (LKPD) Praktikum IPA Berbasis Bring Your Own Device (BYOD) di Sekolah Dasar - Umar Almahdali, Sarah Diva; Riawarda, Andi; Mirnawati , Mirnawati (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This research is entitled Developing Student Worksheets (LKPD) for Bring Your Own Device (BYOD) Based Science Practicum for Class V at SDN 34 Bara, Palopo City. This research aims: (1) To determine the analysis of students' needs for the development of BYOD-based science practicum LKPD for class V at SDN 34 Bara, Palopo City (2) to find out the design of BYOD-based science practicum LKPD for class V at SDN 34 Bara, Palopo City (3) to find out validity and practicality of BYOD-based science practicum LKPD for class V SDN 34 Bara, Palopo City. The research was carried out using the type of development research or Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. This research was conducted at SDN 34 Bara, Palopo City. The subjects in this research were 20 class V educators and students, and the object of this research was (LKPD) BYOD-based science practicum. The data collection techniques used were observation, interviews, and giving questionnaires to educators and students. The data obtained was then analyzed qualitatively and quantitatively. This research produced teaching materials for science practicum LKPD with single and mixed substance materials based on bring your own device (BYOD) which were validated by 3 experts, namely material experts with a score of 93.75% (very valid category), language experts with a score of 91.66 % (very valid category), and design expert with a score of 96.87% (very valid category). For the practicality test, results were obtained from students with a score of 91.79% (very practical category) and educators with a score of 94% (very practical category). This shows that the product developed has a high level of validity, so the product developed by researchers is suitable for use for learning activities in schools.